Antimicrobial Activity of Selected Essential Oils - Miroslava Kačániová; Lucia Galovičová; Veronika Valková; Petra Borotová; Simona Kunová (Scientific Papers Animal Science and Biotechnologies, 2023)
Essential oils are natural, aromatic and volatile liquids, which are frequently obtained by steam or water distillation from plants. In general, they have a pleasant odor and their proven antimicrobial, antiviral, antifungal, antioxidant, antifungal, insecticidal and antiparasitic properties have been known for several years. The aim of this work was to monitor antimicrobial activity against pathogenic microorganisms using two methods. The antimicrobial activity of essential oils was determined using the disk diffusion method and the broth dilution method. We found that wild thyme and peppermint essential oils were the most effective against the gram-negative bacterium Pseudomonas aeruginosa CCM 3955 in both cases with size of an inhibition zone 20.66 mm measured by disk diffusion method. Coriander essential oil had the best antimicrobial activity against all tested pathogenic microorganisms in the range of concentrations from 0.75 µg.ml-1 to 13.35 µg.ml-1 with broth dilution method.